2007
DOI: 10.1038/modpathol.3800965
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-specific downregulation and methylation of the CDH13 (H-cadherin) and CDH1 (E-cadherin) genes correlate with aggressiveness of human pituitary adenomas

Abstract: The gene products of CDH13 and CDH1, H-cadherin and E-cadherin, respectively, play a key role in cell-cell adhesion. Inactivation of the cadherin-mediated cell adhesion system caused by aberrant methylation is a common finding in human cancers, indicating that the CDH13 and CDH1 function as tumor suppressor and invasion suppressor genes. In this study, we analyzed the expression of H-cadherin mRNA and E-cadherin protein in 5 normal pituitary tissues and 69 primary pituitary adenomas including all major types b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
60
2
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 33 publications
5
60
2
4
Order By: Relevance
“…The present study showed that reduced or absent expression of E-cadherin and P120 was associated with the histological grade of tumors, which is consistent with reported data [17][18][19][20][21] . In well-differentiated tumors, there were obvious and strong staining along the cell-cell boundaries, whereas in poorly-differentiated tumors, the immunohistostaining was focally and heterogeneously distributed, with patchy or spotty features along the cellcell boundaries, indicating that the staining of E-cadheri and P120 is related with the differentiation of ICC, namely both E-cadherin and P120 may be regarded as differentiation markers of tumor.…”
Section: Discussionsupporting
confidence: 82%
“…The present study showed that reduced or absent expression of E-cadherin and P120 was associated with the histological grade of tumors, which is consistent with reported data [17][18][19][20][21] . In well-differentiated tumors, there were obvious and strong staining along the cell-cell boundaries, whereas in poorly-differentiated tumors, the immunohistostaining was focally and heterogeneously distributed, with patchy or spotty features along the cellcell boundaries, indicating that the staining of E-cadheri and P120 is related with the differentiation of ICC, namely both E-cadherin and P120 may be regarded as differentiation markers of tumor.…”
Section: Discussionsupporting
confidence: 82%
“…32 Our previous study also demonstrated that tumor-specific downregulation of E-cadherin and H-cadherin related to invasiveness of pituitary adenoma. 27 HMGA2 may be involved in tumor cell The value of let-7 expression in normal pituitary tissues was equal to onefold. The reduced expression of let-7 was found in 23 (41.8%) adenomas (blue square columns, downregulation rates were À1.10 to À16.41-fold, 17 cases showed over 2-fold change).…”
Section: Discussionmentioning
confidence: 99%
“…26,27 After deparaffinization and antigen retrieval using an autoclave oven technique, sections were incubated at 41C overnight with goat polyclonal anti-HMGA2 antibody (1:50; HMGI-C, S-15, Santa Cruz Biotechnology, Santa Cruz, CA, USA) or with Ki-67 antigen mouse monoclonal antibody (1:100; DakoCytomation, Glostrup, Denmark). Antigen-antibody complexes were detected using the cobalt-3,3 0 -diaminobenzidine reaction.…”
Section: Immunohistochemicalmentioning
confidence: 99%
“…1,2 Hypermethylation of gene promoter regions has been implicated in the inactivation of several genes, including p16/ CDKN2A, RB1, DAPK, GADD45g, RASSF1A, E-cadherin, H-cadherin, Ikaros, and FGFR2. [3][4][5][6][7][8][9][10][11] GSTP1 encodes glutathione-S-transferase-p, a member of a family of enzymes, the glutathione-S-transferases (GSTs) that function as dimers composed of subunits from five main classes: a, m, p, s, and y. GSTs are phase 2 enzymes that catalyze the conjugation of glutathione with electrophilic and hydrophobic compounds including carcinogens, natural toxins, and exogenous drugs. [12][13][14] GSTs are believed to play an important role in protecting cells from cytotoxic and carcinogenic agents.…”
mentioning
confidence: 99%